Reconsidering Constitutional Formation II Decisive Constitutional Normativity: From Old Liberties to New Precedence - Müßig, Ulrike (Studies in the History of Law and Justice, 2018)
Precedence of Constitution; Normativity and Constitution; Constitutional History of Europe; Constitutionality of Revolutions; American Constitutional History; Constitutional Normativity; Fundamental Laws; Old Liberties in European History; Unconstitutionality of Statutes; Judicial Review; Normativity and Precedence; Constitutional Precedence of the 3 May System; Constitutional Precedence and Polish Substantial Criminal Law; 1815 Constitution of the Kingdom of Poland; Belgian Constitution of 1831; 1815 Constitution of the United Kingdom of the Netherlands; Constituent Power and Constitutionalism in 19th Century Norway; Spirit of the Albertine Statute; Hans Kelsen and Adolf Julius Merkl